Edmund Krüger and his archaeological collection from Lithuania in the Courland Province Museum - Vasiliauskas, Ernestas (Archaeologia Lituana, 2015)
Edmund Carl Julius Krьger (1836–1909), pedagogue, archaeologist, collector, and state advisor, was born in Tartu. His father was Woldemar Friedrich Krьger, a drawing teacher, an artist (a representative of the Baltic German artists (deutschbaltischer Maler) of the Tartu school and of the realism and Biedermeier styles), and an Estonian lithographic pioneer; his mother was Emilie Dorothea (nйe Rimmann). He studied chemistry at the University of Tartu during 1855–1859, graduating in 1860. E. Krьger married Mathilie Wilhelmine Luise Kiehnast (born in Tartu in 1833) in 1861and had seven children by her. In 1861, he arrived in Jelgava (Mitau) (Fig. 2) to live and work, spending the largest part of his life, 48 years, there.E. Krьger was a member of the Literature and Art Society of Courland (Kurländischen Gesellschaft für Literatur und Kunst; hereinafter the Society) during 1863–1909 and Courland Province Museum (Kurländischen Provinzial Museum; hereinafter the KPM) (Figs. 3, 4) during 1897–1909. During 1898–1908 he headed the KPM Mineral and Flora Section and belonged to the Prehistoric Antiquities Section (headed by Carl Boy (1898) and Georg Wiedemann (beginning in 1899). He participated in complex expeditions together with other Society members. For example, it is known that on 14 April 1866 August Bielenstein, together with clergyman August von Raison, E. Krьger, Julius Dцring, and others (Rutkowsky) conducted excavations at Tērvete (Hofzumberge) and Svētais kalns (Heiligenberg) hillforts. Whether he participated with other members in complex expeditions in North Lithuania is unknown. While working at Jelgava Realschule (Fig. 1) as a senior teacher, he used to learn about ancient sites (for example, Lokava) from the pupils. In around 1865 E. Krьger joined the investigation of ancient sites and began to accumulate archaeological finds, mostly from Courland and Kaunas Provinces (Lith. gubernija). In about 1895 the collection must have been complete (Fig. 5). It was well looked after and each find spot was recorded. (The fate of the list of finds is unknown.) E. Krьger, as shown in his obituary, had accumulated a rich collection of natural, archaeological, and historical artefacts as well as manuscripts, coins, and other antique rarities (Rigasche, 1909, S. 5; Dьna, 1909, S. 5). In 1901 KPM bought his collection of 1200 finds (184 stone artefacts (123 axes with a shaft hole, 22 celts, and fire strikers), 867 metal artefacts (219 iron, 648 bronze, 9 silver (5 heart-shaped brooches, 2 pendants, 1 bracelet, and 1 ring), 42 cowry shells, 27 amber beads, 26 glass beads, 9 ‘urn’ sherds, and a multitude of other items (Sitzungsberichte, 1903, S. 49–50).He should be known to Lithuania as the owner of the largest collection of archaeological finds from Lithuania (138 artefacts, 11% of the entire collection), which was acquired by KPM in 1901. The biggest part of it consisted of 1st–17th-century finds collected at nine localities (Deglėnai, Glebava, Karašilis, Pakruojis, Paliečiai, Ramygala, Suginčiai, and Zarasai Neighbourhoods (Lith. apylinkė), there being no data about other localities). The E. Krьger collection also included a collection of flint and stone axes and bore cores (54 artefacts) from various Lithuanian localities, beginning with then Zarasai (Nowoaleksandrowsk) County and ending with Telšiai and Marijampolė–Kalvarija Neighbourhoods (from 30 identified find spots) (Figs. 5–14) (Table 1). The finds were mainly collected from then Panevėžys County, where the mostly German landlords, many of them also Society and KPM members, had manors. It is difficult to say how the artefacts were collected. It is very likely that E. Krьger acquired these collections by visiting North Central Lithuanian manors (mostly in Pakruojis and Žeimelis Neighbourhoods, which belonged to von der Ropp and von Grotthuss). The Suginčiai finds were probably acquired during the 1883 expedition to Lokava. Some of the finds were apparently given to him by pupils from Lithuania who were studying in Jelgava. It is likely that some were acquired from other collectors. The possibility should not be rejected that E. Krьger could have excavated some archaeological sites that were being destroyed.There is only one publication about ancient Lithuanian sites, i.e. the 1883 issue about Lokava hillfort (Akmenė District). In all, six bibliographical items are ascribed to E. Krьger during 1865–1883. These describe the excavations conducted in the vicinity of Kalnamuiža (Hofzumberge, Tērvete) masonry castle and the artefacts discovered there (1865–1866), the Sesava (Krons Sessau) stone axes (1866), a skull found at Tērvete old cemetery (1868), and a paper, read at a 1865 Society session, about the work of Constantin Caspar Andreas von Grewingk (1819–1887), Das Steinalter der Ostseeprovinzen Liv-, Esth- und Kurland und einiger angrenzenden Landstriche (Dorpat, 1865), and stone artefacts preserved in KPM.In classifying his Lithuanian material on the basis of the sites, 2 barrow cemeteries and 15th–16th-century old cemeteries created later in them, 5 cemeteries, 1 hillfort, and 2 manor sites were distinguished, their chronology ranging from the Late Neolithic – 1st century ad to the 17th century. E. Krьger’s contribution to Lithuanian research lies in the abundance of the archaeological material he accumulated and in the information it provides.Vertė Jeffrey Arthur Bakanauskas